Part 3. (1st June 2015) - Stengers, Isabelle; Davis, Christine; Lyall, Scott; Deleuze, Gilles; Parnet, Claire; Lanthier, Daniel; Zizek, Slavoj; Cubitt, Sean
Entries: The Pick-Up, "Don't Bifurcate", Primary Colours, Touché-Touchant, Entropy, Redaction, Non-Colour, Mixture. Includes text by Isabelle Stengers, Christine Davis, Scott Lyall, Gilles Deleuze and Claire Parnet, Daniel Lanthier, Slavoj Zizek, Sean Cubitt. Artworks by Donald Weber, Odilon Redon, Patrick Syme, Claude Tousignant, Liz Deschenes, Steve McQueen, Frederik DeWilde, Pascale Marthine Tayou.